Cathode material and preparation method thereof, cathode and method for recovering metal in copper anode slime
By filling the cathode material of the porous conductive material with hydrophobic ionic liquid, combining physical, chemical and electrosorption, the problems of low equipment utilization and low adsorption capacity in copper anode mud recovery are solved, and efficient and low-cost recycling of valuable metals are achieved.
Patent Information
- Application Number
- CN202510752161.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-08-08
AI Technical Summary
The existing copper anode mud recovery methods have problems with low equipment utilization and exhaust gas emissions. The traditional electrode adsorption capacity is low and the cost is high, making it difficult to efficiently recover valuable metals in complex solutions.
The cathode material of the porous conductive material is filled with hydrophobic ionic liquid. Through the coupling of physical adsorption, chemical adsorption and electro-adsorption, combined with the electrodeposition process, it is highly designed and suitable for metal ion recovery under different conditions.
It has achieved efficient enrichment of rare and precious metals in copper anode mud, with simple operation and low operating cost. It is suitable for step-by-step electrodeposition of a variety of metal ions and has stable circulation use.
Smart Images

Figure CN120443275A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of resource recovery, and in particular to a cathode material and a preparation method thereof, a cathode, and a method for recovering metal from copper anode mud. Background Art
[0002] Electrolytic refining uses copper produced by fire refining as the anode, stainless steel or thin copper sheets produced by electrolysis as the cathode, and an aqueous solution of copper sulfate and sulfuric acid as the electrolyte. Under the action of direct current, the anode copper electrochemically dissolves, and the copper ions in the solution are precipitated at the cathode. Depending on the electrochemical properties, impurities do not dissolve at the anode and enter the anode mud, or impurities dissolve at the anode but remain in the electrolyte and are not precipitated by the cathode. Among them, positively charged metals (gold, silver, platinum group metals) and elements in the form of compounds (oxygen, sulfur, selenium, etc.) do not undergo electrochemical dissolution at the anode but fall to the bottom of the tank in an extremely finely dispersed state. A small amount of silver will react with the electrolyte to produce silver sulfide precipitate. If there is Cl in the electrolyte - , it will precipitate into the anode mud in the form of silver chloride.
[0003] Current methods for recovering copper anode slime include traditional pyrometallurgical processes, integrated metallurgical processes, and hydrometallurgical processes. While pyrometallurgical processes offer a high throughput, insufficient copper anode slime production at many small and medium-sized smelters leads to idle equipment and low utilization, significantly limiting the use of pyrometallurgical processes. The roasting pretreatment method in the integrated metallurgical process inevitably generates waste gas and dust emissions. The ammonia, formaldehyde, and Cl2 used in the wet separation and recovery of Au and Ag are all toxic. Furthermore, the large amount of wastewater generated by leaching, containing heavy metals, chlorine, and ammonia nitrogen, often requires costly recovery and treatment. Furthermore, the hydrometallurgical process cannot rely on O2 to remove base metals.
[0004] Traditional platinum electrode has a smooth surface, relies only on electrochemically active sites, and has low adsorption capacity. It also relies on the difference in redox potential of metals, has limited selectivity, is easily affected by interfering ions, is relatively expensive, and is not suitable for the electrical extraction of valuable metals in complex solutions. Summary of the Invention
[0005] The invention discloses a cathode material and a preparation method thereof, a cathode and a method for recovering metal from copper anode mud, in order to solve the above technical problems in the prior art.
[0006] In order to solve the above problems, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present application provides a cathode material, the preparation of which includes a hydrophobic ionic liquid, a porous conductive material and an encapsulation material; wherein,
[0008] The hydrophobic ionic liquid is filled in the pores of the porous conductive material;
[0009] The packaging material is coated on the outside of the porous conductive material to encapsulate the hydrophobic ionic liquid in the pores of the porous conductive material.
[0010] Furthermore, the weight percentage of the hydrophobic ionic liquid is 45%-55%,
[0011] The weight percentage of the porous conductive material is 35%-45%,
[0012] The weight percentage of the packaging material is 1%-5%;
[0013] The sum of the mass percentages of the hydrophobic ionic liquid, the porous conductive material and the packaging material is 100%.
[0014] Furthermore, the hydrophobic ionic liquid comprises:
[0015] a) The cationic portion is a derivative cation with an imidazolium cation as a skeleton, modified by any one or more of an amino group, a quaternary ammonium group, a quaternary phosphonium group, a thiourea substituent, a thioether substituent, a sulfhydryl group, a disulfide functional group, and a metal ion chelating group;
[0016] b) The anion portion is at least one selected from bis(trifluorosulfonyl)imide, tetrafluoroborate, hexafluorophosphate, hypochlorite, trifluoroacetic acid, dicyandiamide, bromide, and chloride.
[0017] Furthermore, the porous conductive material is selected from any one of metal-based porous materials, carbon-based porous materials, metal-organic framework derivatives and porous conductive ceramics;
[0018] And / or, the packaging material includes a hydrophobic organic polymer material.
[0019] Furthermore, the packaging material is selected from any one of polytetrafluoroethylene, fluorinated ethylene propylene copolymer, perfluoroalkoxy resin and perfluorosulfonic acid polymer.
[0020] In a second aspect, the present application provides a method for preparing a cathode material, characterized in that it comprises the following steps:
[0021] A1. Immersing the porous conductive material in a hydrophobic ionic liquid so that the hydrophobic ionic liquid fully enters the pores of the porous conductive material;
[0022] A2. Coating a packaging material layer on the outside of the porous conductive material treated in step A1, and drying the layer to obtain a cathode material.
[0023] Furthermore, in step A1, the immersion is carried out under a negative pressure environment of 0.3-0.8 MPa for 22-26 hours;
[0024] And / or, in step A2, coating the encapsulation material layer is performed by immersing the porous conductive material treated in step A1 in an encapsulation material solution, wherein the weight percentage concentration of the encapsulation material solution is 1%-10%;
[0025] And / or, in step A2, the drying is carried out in a vacuum environment at a temperature of 55-65° C. for 0.5-1.5 hours.
[0026] In a third aspect, the present application provides a cathode prepared by the cathode material prepared by the above preparation method.
[0027] In a fourth aspect, the present application provides a method for recovering metals from copper anode mud, comprising the following steps:
[0028] B1. The copper anode mud is ground, sieved, and acid-leached using a H2SO4-MnO2 system to obtain anode mud leachate;
[0029] B2. Controlling the temperature of the anode mud leachate obtained in step B1 to be 15-60° C. and the pH to be 0-7, then placing the cathode described in claim 8 in the anode mud leachate and soaking it for 0.5-36 hours to perform a first enrichment of rare and precious metals in the anode mud leachate; then, connecting an external power supply in the presence of the anode and applying a voltage of 1-30 V to perform a second enrichment of rare and precious metals in the anode mud leachate.
[0030] Furthermore, in the step B1, during acid leaching, the solid-liquid mass ratio of the sieved copper anode mud powder to the H2SO4-MnO2 system is 1:5-1:10.
[0031] Furthermore, in the step B1, in the H2SO4-MnO2 system, MnO2 accounts for 40-70% by dry weight, and the H2SO4 concentration is 0.7-1.4 mol / L;
[0032] And / or, in step B1, during acid leaching: the leaching temperature is 65-85° C., the stirring speed is 500-750 r / min, and the leaching time is 4-12 h;
[0033] And / or, in step B2, the anode is selected from any one of a graphite electrode, a Pt electrode and a lead dioxide electrode;
[0034] And / or, in step B2, the rare metals enriched for the first time and the rare metals enriched for the second time are the same.
[0035] The principle of acid leaching in this application is as follows: Acid leaching extracts metal elements by chemically reacting an acidic solution with metal-containing raw materials (such as ore and anode mud). This chemical reaction converts the commonly present metal elements in the anode mud, such as gold, silver, and platinum group metals, as well as other metal elements such as Cu, Sb, and Bi, into soluble ions that enter the solution, thereby achieving metal separation and recovery. The core mechanism is based on dissolution and redox reactions under acidic conditions. Organic matter is oxidized to small molecules such as CO2, while sulfides and chlorides are reduced to H2S or Cl2, neither of which participates in the electrodeposition process. Dissolution primarily involves the dissolution of the metal elements.
[0036] The principle of electrodeposition in this application is that during the electrodeposition process, by controlling the electrode potential, current density, solution pH, temperature, additives and other conditions, the difference in reduction potential of different metal ions can be used to achieve selective precipitation. This is a complex process that requires the control of multiple parameters such as the solubility state of the metal in the solution, solution pH, electrolysis voltage, etc. For example, the key is the regulation based on the standard reduction potential. The standard reduction potential (E 0 ) determines the order of precipitation. For example:
[0037] Cu²⁺ / Cu:E 0 = +0.34 V
[0038] Ni²⁺ / Ni:E 0 = -0.25 V
[0039] Ag⁺ / Ag:E 0 = +0.80 V
[0040] In a mixed solution, metals with higher reduction potentials (such as Ag⁺) will precipitate preferentially.
[0041] Adjust the pH value of the solution. The pH value affects the existence form and precipitation potential of metal ions:
[0042] Adjusting additives: Adding ammonia (NH3) causes Cu²⁺ to form a [Cu(NH3)4]²⁺ complex, reducing the effective concentration and delaying precipitation. Using cyanide (CN⁻) to complex Ag⁺ and Au⁺ significantly reduces their precipitation potential (e.g., AgCN⁻ complex).
[0043] Only by combining all parameters can the effective control of metal ion precipitation in solution be achieved. Example:
[0044] Example of a step-by-step electrodeposition process:
[0045] Take a mixed solution containing Cu²⁺, Ni²⁺, and Ag⁺ as an example:
[0046] Step 1 (Ag recovery):
[0047] The voltage is controlled to be slightly higher than the reduction potential of Ag⁺ (about +0.8 V), the pH is acidic (pH=0.5-1.5), the electrolyte temperature is adjusted to 25~35℃, and CN⁻ is added to complex other metals (such as Cu and Ni).
[0048] After Ag is precipitated, replace the electrolyte or adjust the conditions.
[0049] Step 2 (Cu recovery):
[0050] Adjust the pH of the electrolyte in the first step to acidic (pH = 1–2) to dissolve the complexed metal. Adjust the electrolyte temperature to 40–60°C and apply a voltage to the Cu²⁺ precipitation potential (approximately +0.34 V) to recover Cu.
[0051] After Cu is precipitated, replace the electrolyte or adjust the conditions.
[0052] Step 3 (Ni recycling):
[0053] Reduce the voltage to below -0.25 V, increase the temperature to 60-70°C, and add boric acid to improve the coating.
[0054] The technical solution adopted by the present invention can achieve the following beneficial effects:
[0055] (1) The cathode material in this application can be designed according to the metal ions that need to be recovered, and the functional groups of the hydrophobic ionic liquid in the cathode material can be specifically designed. The designability is strong, and the hydrophobic liquid can be changed according to different conditions to meet the design requirements under different usage conditions. In addition, the synthesis process of the hydrophobic ionic liquid is simple.
[0056] (2) The cathode material in the present application can be prepared into a cathode for recovering metal ions in copper anode mud. During the use of the electrode, physical adsorption, chemical adsorption and electrical adsorption are coupled, which can efficiently enrich the rare and precious metal components in the leachate. The enrichment effect of the target metal ions is enhanced through the organic coupling of physical adsorption, chemical adsorption and electrical adsorption. Specifically, physical adsorption mainly relies on the porous structure and high specific surface area of the porous conductive material in the electrode structure to quickly capture the valuable metal ions in the solution; chemical adsorption selectively binds to specific metal ions through the functional groups in the hydrophobic ionic liquid, thereby recovering specific metal ions. For example, the thiourea group can be used to absorb Au. 3+ The specific binding is carried out to improve the gold extraction efficiency during the electrodeposition process, while the electrosorption enhances the migration and enrichment efficiency of ions through the electric field. The present application improves the recovery efficiency of the electrode in the recovery of valuable metals through the synergistic effect of rapid enrichment by physical adsorption, deep fixation by chemical adsorption, and continuous replenishment of ions driven by the electric field.
[0057] (3) The cathode material in the present application can be used to prepare a cathode that can be used to recover metal ions in copper anode mud. It has a wide operating voltage range and can remain stable and work normally in the voltage range of 0.5 V to 12 V. Since the raw materials used are stable, they can be recycled, and the recycling of the electrode does not affect the enrichment effect, and the enrichment of different cations can be achieved under different operating conditions; and methods such as controlling different voltages and changing the solution pH can achieve step-by-step electrodeposition of different metal ions. In the application of recovering metal ions in copper anode mud, the metal with the highest specific recovery value is generally the metal.
[0058] (4) The cathode material in this application can be used to prepare a cathode that can be used to recover metal ions in copper anode mud. The operation is simple and the operating cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0060] Figure 1 This is a schematic diagram of how to use the cathode;
[0061] Figure 2 Schematic diagram of filling the porous carbon conductive material with the hydrophobic ionic liquid [HMIm] Tf2N in the experimental example;
[0062] Figure 3 This is a schematic diagram of the cathode enrichment efficiency after 10 cycles in the experimental example;
[0063] Figure 4 This is the infrared structural information diagram of the ionic liquid inside the cathode before and after voltage is applied in the experimental example.
[0064] In the figure: 1. Copper anode mud leachate; 2. Cathode; 3. Anode; 4. Wire; 5. Power supply. DETAILED DESCRIPTION
[0065] To make the objectives, technical solutions, and advantages of the present invention more apparent, the technical solutions of the present invention will be described in detail below. Obviously, the embodiments described are only some of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other implementations obtained by those of ordinary skill in the art without inventive effort are within the scope of protection of the present invention.
[0066] Ingredients Description:
[0067] The hydrophobic ionic liquid [A-336][TS] in Example 2 was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0068] The hydrophobic ionic liquid [Hmim][PF6] in Example 3 was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0069] The hydrophobic ionic liquid used in Example 4: [BMIM][PF6] (cation: 1-butyl-3-methylimidazolium anion: [PF6] - ) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0070] The hydrophobic ionic liquid used in Example 5: [EMIM][TFSI] (cation: 1-ethyl-3-methylimidazolium anion: [TFSI] - ) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0071] The hydrophobic ionic liquid used in Example 6: [P 66614 ][TFSI] (cation: trihexyltetradecyl anion: [TFSI] - ) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0072] The hydrophobic ionic liquid used in Example 7: [C8Py][BETI] (cation: N-octylpyridinium anion: [BETI] - ) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0073] The hydrophobic ionic liquid used in Example 8: [N 4441 ][BPh4] (cation: tetrabutylammonium anion: [BPh4] - ) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0074] Of course, hydrophobic ionic liquids can also be synthesized by chemical methods.
[0075] 1. Implementation
[0076] Example 1:
[0077] The cathode is used as follows Figure 1 As shown, it includes MOF conductive material and hydrophobic ionic liquid [C6MIm][DDTC]; the hydrophobic liquid is filled in the air of the MOF conductive material, and then the MOF conductive material is pressed into a sheet to form an electrode.
[0078] 1.1 Raw materials:
[0079] Hydrophobic ionic liquid: [C6MIm][DDTC], with a weight percentage of 54%;
[0080] Porous conductive material: MOF conductive material, with a weight percentage of 43%;
[0081] Packaging material: polytetrafluoroethylene, the weight percentage is 3%.
[0082] ①Synthesis of MIL-101 porous conductive material (Synthesis of MIL-101 porous conductive material in aqueous phase)
[0083] Dissolve 0.744g Zn(NO3)6H2O in 10ml deionized water to obtain a zinc nitrate solution; dissolve 12.3g 2-methylimidazole in 90ml deionized water to obtain a ligand solution;
[0084] The zinc nitrate solution was mixed with the ligand solution under stirring, and after reacting for 1 hour, the product was collected by centrifugation;
[0085] The collected product was washed three times with methanol; then the product was vacuum dried at 150° C. for 24 hours to obtain a fine powder of MIL-101 porous conductive material.
[0086] ②Synthesis of hydrophobic ionic liquid [C6MIm][DDTC]:
[0087] 1-Hexyl-3-methylimidazolium chloride ([C6MIm]Cl):
[0088] 100 ml of N-methylimidazole and 100 ml of n-chlorohexane were weighed separately in a round-bottom flask and refluxed at 70°C with magnetic stirring for 24 h to obtain a crude product. The crude product was washed with ethyl acetate 4-5 times to remove unreacted N-methylimidazole and n-chlorohexane, and then the ethyl acetate was removed by rotary evaporation at 80°C. After vacuum drying at 80°C for 24 h, a colorless, transparent, viscous liquid [C6MIm]Cl was obtained.
[0089] 1-Hexyl-3-methylimidazole-2-ethyl-2-thiocarbamate ([C6MIm][DDTC]):
[0090] [C6MIm]Cl and sodium diethyldithiocarbamate (DDTC) were weighed in a molar ratio of 1:15 and dissolved in an appropriate amount of acetonitrile (1.5 times the total volume of [C6MIm]Cl and sodium diethyldithiocarbamate (DDTC). The mixture was then added to a round-bottom flask. The mixture was stirred at 3000 rpm under a nitrogen atmosphere at 65°C for 12 hours before being stopped. The precipitated NaCl was removed by filtration, and the acetonitrile was then removed by vacuum distillation using a rotary evaporator to obtain a crude product. The crude product was dissolved in chloroform and rinsed five times with deionized water to remove any unreacted starting material. The chloroform was then removed by rotary evaporation, and the mixture was dried in a vacuum drying oven at 60°C for 24 hours to obtain a reddish-brown, transparent, viscous liquid [C6MIm][DDTC].
[0091] 1.2 Preparation of cathode materials
[0092] IL@MIL-101 was prepared by the immersion-negative pressure method. The specific steps are as follows:
[0093] A1. Dissolve 0.06 g and 39 μL of [C6MIm][DDTC] hydrophobic ionic liquid in a glass bottle containing 6 mL of anhydrous methanol. Slowly add 0.05 g of the fine powdered MIL-101 porous conductive material prepared in 1.1 while stirring at a stirring rate of 3000 rpm. After addition, stir at room temperature for 1 hour. Then, raise the temperature to 60°C and apply a negative pressure of 0.5 MPa. The MIL-101 porous conductive material continues to be immersed in the [C6MIm][DDTC] hydrophobic ionic liquid for 24 hours. Filter and then dry in a vacuum environment at 55°C for 1.5 hours to obtain the treated porous conductive material ([C6MIm][DDTC]@MIL-101 composite powder material).
[0094] A2. The [C6MIm][DDTC]@MIL-101 composite powder material obtained in step A1 was immersed in an encapsulation material solution for 30 minutes. The encapsulation material solution was a 1% by weight polytetrafluoroethylene solution prepared by 0.003 g of polytetrafluoroethylene and pure water. After the impregnation was completed, the composite powder material was removed and then dried in a vacuum environment at 60°C for 1 hour to obtain a cathode material (IL@MIL-101 electrode material).
[0095] 1.3. Preparation of cathode
[0096] Take 100 mg of the IL@MIL-101 electrode material prepared in 1.2 and press it into a tablet to make an electrode.
[0097] 1.4. Recovery of metals from copper anode mud
[0098] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 100-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:7. In the H2SO4-MnO2 system, MnO2 accounts for 50% of the dry weight, and the H2SO4 concentration is 0.9 mol / L. The acid leaching is carried out at a stirring speed of 500 r / min and a leaching temperature of 80°C for 6 hours to obtain an anode mud leachate.
[0099] B2. Recover Au. Control the temperature of the anode mud leachate to 20°C and the pH to 3.0 (the pH can be adjusted by a low-concentration sodium hydroxide solution, such as a 5% by mass sodium hydroxide solution). Without an external power supply, immerse the cathode in the anode mud leachate for 26 hours to enrich the Au in the anode mud leachate for the first time. Then, use the graphite electrode as the anode and apply a 2.5V power supply to continue enriching the Au in the anode mud leachate for 20 minutes, and then enrich the Au in the anode mud leachate for the second time.
[0100] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without adding a power source, and the anode mud leachate after enrichment with a power source were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 1 below. The test values in Table 1 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0101] Table 1 Example 1 process detection data table:
[0102] content Au Ag Se Te Bi Copper anode mud 1.8% wt 12.5% wt 11.1% wt 1.6% wt 1.3% wt Target powder 3.7% wt 23.4% wt 18.1% wt 5.6% wt 2.3% wt Anode mud leachate 2.7% wt 21.4% wt 14.3% wt 3.1% wt 1.1% wt Anode mud leachate after enrichment without power supply 2.25% wt 18.4% wt 18.1% wt 4.6% wt 2.1% wt Anode mud leachate after power enrichment 0.2% wt 13.4% wt 11.1% wt 1.6% wt 1.3% wt
[0103] It can be seen from Table 1 that without an external power supply, the Au enrichment effect reached 17%; then, with an external power supply for enrichment treatment, the Au enrichment effect reached 93%.
[0104] Example 2:
[0105] The cathode is used as follows Figure 1 As shown, it includes a carbon-based conductive material (graphene aerogel material is selected) and a hydrophobic ionic liquid [A-336][TS]; the hydrophobic liquid is filled in the carbon-based conductive material and then coated on a copper electrode to form an electrode.
[0106] 2.1 Raw materials:
[0107] Hydrophobic ionic liquid: [A-336][TS], 50% by weight;
[0108] Porous conductive material: carbon-based conductive material - graphene aerogel material, the weight percentage of which is 45%;
[0109] Packaging material: Fluorinated ethylene propylene copolymer, 5% by weight.
[0110] ① Use purchased hydrophobic ionic liquid [A-336][TS]
[0111] In addition, a method for synthesizing a hydrophobic ionic liquid [A-336][TS] is provided:
[0112] Methyltrioctyl ammonium thiosalicylate ([A-336][TS]) is synthesized by the reaction of Aliquat-336, thiosalicylic acid and sodium hydroxide.
[0113] Equimolar amounts of Aliquat-336 and thiosalicylic acid were dissolved in concentrated sodium hydroxide (12 M). The mixture was then stirred continuously in a water bath for 4 hours, maintaining the reaction mixture temperature at 60°C. After the reaction was complete, the mixture was transferred to a separatory funnel and the layers separated. The organic phase was separated and washed thoroughly with deionized water, and the ionic liquid was then dried under vacuum.
[0114] 2.2 Preparation of cathode materials
[0115] A1, 0.02 g, and 17 μL of hydrophobic ionic liquid were placed in a glass bottle, and 0.018 g of porous conductive material was slowly added while stirring at a stirring rate of 3000 rpm. After the addition, the porous conductive material was stirred at room temperature for 0.5 h. The temperature was then raised to 60° C., and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure environment of 0.6 MPa for 23 hours to allow the hydrophobic ionic liquid to fully enter the pores of the porous conductive material. The mixture was filtered and then dried in a vacuum environment at a temperature of 60° C. for 1.5 h to obtain the treated porous conductive material.
[0116] A2. Immerse the porous conductive material treated in step A1 in a packaging material solution for 30 minutes. The packaging material solution is a 5% by weight fluorinated ethylene propylene copolymer solution prepared by 0.002 g of fluorinated ethylene propylene copolymer and pure water. After the immersion is completed, take it out and then dry it in a vacuum environment at a temperature of 60°C for 1.5 hours to obtain a cathode material.
[0117] 2.3. Preparation of cathode
[0118] Take 100 mg of the cathode material prepared in 2.2 and press it into a tablet to make an electrode.
[0119] 2.4. Recovery of metals from copper anode mud
[0120] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 50-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:10. In the H2SO4-MnO2 system, MnO2 accounts for 60% of the dry weight, and the H2SO4 concentration is 1.0 mol / L. The acid leaching is carried out at a stirring speed of 650 r / min and a leaching temperature of 80°C for 12 hours to obtain an anode mud leachate.
[0121] B2. Recover Ag by controlling the temperature of the anode mud leachate to 25°C and the pH to 1.5 (the pH can be adjusted by a low-concentration sodium hydroxide solution, such as a sodium hydroxide solution with a mass percentage concentration of 5%). Without an external power supply, immerse the cathode in the anode mud leachate for 26 hours to enrich the Ag in the anode mud leachate for the first time. Then, use the Pt electrode as the anode and apply a 2.7V power supply to continue enriching the Ag in the anode mud leachate for 30 minutes, and then enrich the Ag in the anode mud leachate for the second time.
[0122] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without adding a power source, and the anode mud leachate after enrichment with a power source were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 2 below. The test values in Table 2 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0123] Table 2 Example 2 process detection data table:
[0124] content Ag Au Se Te Bi Copper anode mud 23.5% wt 1.8% wt 12.1% wt 1.8% wt 1.4% wt Target powder 33.5% wt 2.1% wt 15.2% wt 2.9% wt 2.5% wt Anode mud leachate 30.1% wt 1.9% wt 13.1% wt 2.7% wt 2.3% wt Anode mud leachate after enrichment without power supply 26.5% wt 2.1% wt 11.2% wt 2.4% wt 2.1% wt Anode mud leachate after power enrichment 0.5% wt 1.3% wt 11.2% wt 1.4% wt 1.2% wt
[0125] It can be seen from Table 2 that without an external power supply, the Ag enrichment effect reached 12%; then, with an external power supply for enrichment treatment, the Ag enrichment effect reached 98%.
[0126] Example 3:
[0127] 3.1 Raw materials:
[0128] Hydrophobic ionic liquid: [Hmim][PF6], with a weight percentage of 55%;
[0129] Porous conductive material: carbon nanotubes, 40% by weight;
[0130] Packaging material: perfluorosulfonic acid polymer, the weight percentage of which is 5%.
[0131] ① Use purchased hydrophobic ionic liquid [Hmim][PF6]
[0132] In addition, a method for synthesizing a hydrophobic ionic liquid [Hmim][PF6] is provided, and the synthesis method is as follows:
[0133] Weigh 1-methylimidazole and bromohexane in equal molar ratios, react at 60°C for 24 hours, wash three times with ethyl acetate, remove a small amount of ethyl acetate with a rotary evaporator, and dry in a vacuum oven at 60°C for 24 hours to obtain [Hmim][Br].
[0134] Weigh equal molar ratios of [Hmim][Br] and KPF6 and dissolve them in water, react at 60℃ for 24h, separate the aqueous phase, and vacuum dry in a 60℃ oven for 72h to obtain the product [Hmim][PF6]
[0135] 3.2 Preparation of cathode materials
[0136] A1. Take 5 mg of the above carbon nanotubes and immerse them in 10 mg of hydrophobic ionic liquid [Hmim][PF6], sonicate for 30 min, heat to 90°C and stir for 24 h; wash twice with ethyl acetate, remove excess ethyl acetate by rotary evaporation, and dry in a vacuum oven at 60°C for 24 h.
[0137] A2. Immerse the [Hmim][PF6]@ carbon nanotube composite powder material obtained in step A1 in a 2%wt perfluorosulfonic acid polymer solution for 30 minutes, take it out, and dry it in a vacuum environment at 60°C for 1 hour to obtain an electrode material.
[0138] 3.3 Preparation of cathode
[0139] Take 34 μL of the cathode material prepared in 3.2 and apply it on a 1 cm 2 The electrode with IL supported on porous carbon was dried on carbon cloth.
[0140] 3.4. Recovery of metals from copper anode mud
[0141] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 120-mesh sieve. The sieved material is the target powder. The target powder is acid-leached using a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:5. In the H2SO4-MnO2 system, MnO2 accounts for 55% of the dry weight, and the H2SO4 concentration is 1.0 mol / L. The acid leaching is carried out at a stirring speed of 600 r / min and a leaching temperature of 80°C for 12 hours to obtain an anode mud leachate.
[0142] B2. Recover Bi by controlling the temperature of the anode mud leachate to 25°C and the pH to 0.5 (the pH can be adjusted using a low-concentration sodium hydroxide solution, such as a 5% by mass sodium hydroxide solution). Without an external power supply, immerse the cathode in the anode mud leachate for 12 hours to enrich Bi in the anode mud leachate for the first time. Then, use the Pt electrode as the anode and apply a 1.6V power supply to continue enriching Bi in the anode mud leachate for 25 minutes, and then enrich Bi in the anode mud leachate for the second time.
[0143] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without adding a power source, and the anode mud leachate after enrichment with a power source were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 3 below. The test values in Table 3 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0144] Table 3 Example 3 process detection data table:
[0145] content Bi Au Ag Se Te Copper anode mud 3.8% wt 1.5% wt 12.3% wt 2.1% wt 1.5% wt Target powder 5.8% wt 1.9% wt 13.3% wt 4.2% wt 2.6% wt Anode mud leachate 5.2% wt 1.3% wt 14.1% wt 3.2% wt 2.8% wt Anode mud leachate after enrichment without power supply 4.6% wt 1.1% wt 12.7% wt 3.1% wt 2.2% wt Anode mud leachate after power supply enrichment 0.2% wt 0.7% wt 10.1% wt 1.2% wt 1.8% wt
[0146] It can be seen from Table 3 that without an external power supply, the Bi enrichment effect reaches 12%; then, with an external power supply for enrichment treatment, the Bi enrichment effect reaches 96%.
[0147] Example 4:
[0148] 4.1 Raw materials:
[0149] Hydrophobic ionic liquid: [BMIM][PF6] (cation: 1-butyl-3-methylimidazolium anion: [PF6] - ); its weight percentage is 55%;
[0150] Porous conductive material: metal-based porous material; the weight percentage is 44%;
[0151] Packaging material: polytetrafluoroethylene, the weight percentage is 1%.
[0152] 4.2 Preparation of cathode materials
[0153] A1, 0.22 g, and 160 μL of hydrophobic ionic liquid were placed in a glass bottle, and 0.176 g of porous conductive material was slowly added while stirring at a stirring rate of 2000 rpm. After the addition, the porous conductive material was stirred at room temperature for 1 hour; then the temperature was raised to 70°C, and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure environment of 0.5 MPa for 22 hours to allow the hydrophobic ionic liquid to fully enter the pores of the porous conductive material; the mixture was filtered, and then dried in a vacuum environment at a temperature of 60°C for 1.5 hours to obtain the treated porous conductive material;
[0154] A2. Immerse the porous conductive material treated in step A1 in a packaging material solution for 60 minutes. The packaging material solution is a polytetrafluoroethylene solution with a weight percentage concentration of 1% prepared by 0.004g of polytetrafluoroethylene and pure water; take out after the immersion is completed, and then dry it in a vacuum environment at a temperature of 60°C for 1 hour to obtain a cathode material.
[0155] 4.3. Preparation of cathode
[0156] Take 100 mg of the cathode material prepared in 4.2 and press it into a tablet to make an electrode.
[0157] 4.4. Recovery of metals from copper anode mud
[0158] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 120-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:5. In the H2SO4-MnO2 system, MnO2 accounts for 50% of the dry weight, and the H2SO4 concentration is 0.9 mol / L. During leaching, the leaching temperature is 75°C, the stirring speed is 650 r / min, and the leaching time is 12 h. Obtain anode mud leachate.
[0159] B2. Recover Bi. Control the temperature of the anode mud leachate to 60°C and the pH to 0.5 (the pH can be adjusted using a low-concentration sodium hydroxide solution, such as a 5% by mass sodium hydroxide solution). Without an external power supply, immerse the cathode in the anode mud leachate for 0.5 h to enrich Bi in the anode mud leachate for the first time. Then, use the lead dioxide electrode as the anode and apply a 1.6V power supply to continue enriching Bi in the anode mud leachate for 30 min, and then enrich Bi in the anode mud leachate for the second time.
[0160] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without adding a power source, and the anode mud leachate after enrichment with a power source were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 4 below. The test values in Table 4 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0161] Table 4 Example 4 process detection data table:
[0162] content Bi Au Ag Se Te Copper anode mud 4.2% wt 1.2% wt 10.1% wt 1.4% wt 1.6% wt Target powder 6.1% wt 1.8% wt 10.3% wt 2.1% wt 1.8% wt Anode mud leachate 6.4% wt 1.4% wt 9.1% wt 2.2% wt 2.1% wt Anode mud leachate after enrichment without power supply 4.8% wt 1.2% wt 8.7% wt 1.8% wt 1.9% wt Anode mud leachate after power supply enrichment 0.1% wt 1.1% wt 6.1% wt 1.2% wt 1.6% wt
[0163] It can be seen from Table 4 that without an external power supply, the Bi enrichment effect reached 25%; then, with the external power supply continuing the enrichment process, the Bi enrichment effect reached 98%.
[0164] Example 5:
[0165] 5.1 Raw materials:
[0166] Hydrophobic ionic liquid: [EMIM][TFSI] (cation: 1-ethyl-3-methylimidazolium anion: [TFSI] - ); its weight percentage is 53%;
[0167] Porous conductive material: carbon-based porous material; its weight percentage is 45%;
[0168] Packaging material: fluorinated ethylene propylene copolymer; its weight percentage is 2%;
[0169] 5.2 Preparation of cathode materials
[0170] A1, 0.087 g, and 54.7 μL of hydrophobic ionic liquid were placed in a glass bottle, and 0.067 g of porous conductive material was slowly added while stirring at a stirring rate of 2000 rpm. After the addition, the porous conductive material was stirred at room temperature for 0.5 h. The temperature was then raised to 80° C., and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure environment of 0.3 MPa for 26 hours to allow the hydrophobic ionic liquid to fully enter the pores of the porous conductive material. The mixture was filtered and then dried in a vacuum environment at a temperature of 65° C. for 0.5 h to obtain the treated porous conductive material.
[0171] A2. Immerse the porous conductive material treated in step A1 in a packaging material solution for 90 minutes. The packaging material solution is a 10% by weight fluorinated ethylene propylene copolymer solution prepared by 0.003 g of fluorinated ethylene propylene copolymer and pure water. After the immersion is completed, take it out and then dry it in a vacuum environment at a temperature of 65°C for 0.5 h to obtain a cathode material.
[0172] 5.3. Preparation of cathode
[0173] Take 100 mg of the cathode material prepared in 5.2 and press it into a tablet to make an electrode.
[0174] 5.4. Recovery of Metals from Copper Anode Mud
[0175] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 120-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:8. In the H2SO4-MnO2 system, MnO2 accounts for 50% of the dry basis weight and the H2SO4 concentration is 1.2 mol / L. During leaching, the leaching temperature is 80°C, the stirring speed is 550 r / min, and the leaching time is 6 h. Then, an anode mud leachate is obtained.
[0176] B2. Recover Au. Control the temperature of the anode mud leachate to 15°C and the pH to 3.0 (the pH can be adjusted by a low-concentration sodium hydroxide solution, such as a 5% by mass sodium hydroxide solution). Immerse the cathode in the anode mud leachate for 36 hours without an external power supply to enrich the Au in the anode mud leachate for the first time. Then, use the lead dioxide electrode as the anode and apply a 1.6V power supply to continue enriching the Au in the anode mud leachate for 30 minutes, and then enrich the Au in the anode mud leachate for the second time.
[0177] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without power supply, and the anode mud leachate after enrichment with power supply were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 5 below. The test values in Table 5 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0178] Table 5 Example 5 process detection data table:
[0179] content Au Ag Se Te Bi Copper anode mud 2.8% wt 11.2% wt 9.1% wt 1.8% wt 2.1% wt Target powder 3.7% wt 13.3% wt 8.1% wt 2.6% wt 2.3% wt Anode mud leachate 3.1% wt 11.5% wt 8.2% wt 2.4% wt 1.5% wt Anode mud leachate after enrichment without power supply 2.5% wt 9.4% wt 8.1% wt 1.6% wt 1.2% wt Anode mud leachate after power supply enrichment 0.2% wt 3.4% wt 1.1% wt 1.1% wt 0.5% wt
[0180] It can be seen from Table 5 that without an external power supply, the Au enrichment effect reached 19%; then, with an external power supply for enrichment treatment, the Au enrichment effect reached 94%.
[0181] Example 6:
[0182] 6.1 Raw materials:
[0183] Hydrophobic ionic liquids: [P 66614 ][TFSI] (cation: trihexyltetradecyl anion: [TFSI] - ); its weight percentage is 52%;
[0184] Porous conductive material: metal-organic framework derivative; its weight percentage is 45%;
[0185] Packaging material: perfluoroalkoxy resin; the weight percentage is 3%;
[0186] 6.2 Preparation of cathode materials
[0187] A1, 0.087 g, and 54.7 μL of hydrophobic ionic liquid were placed in a glass bottle, and 0.075 g of porous conductive material was slowly added while stirring at a stirring rate of 3000 rpm. After the addition, the porous conductive material was stirred at room temperature for 0.5 h. The temperature was then raised to 60° C., and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure environment of 0.6 MPa for 23 hours to allow the hydrophobic ionic liquid to fully enter the pores of the porous conductive material. The mixture was filtered and then dried in a vacuum environment at a temperature of 55° C. for 1.5 h to obtain the treated porous conductive material.
[0188] A2. Immerse the porous conductive material treated in step A1 in a packaging material solution for 30 minutes. The packaging material solution is a perfluoroalkoxy resin solution with a weight percentage concentration of 5% prepared by 0.005g of perfluoroalkoxy resin and pure water; take out after the immersion is completed, and then dry it in a vacuum environment at a temperature of 55°C for 1.5 hours to obtain a cathode material.
[0189] 6.3. Preparation of cathode
[0190] Take 100 mg of the cathode material prepared in 6.2 and press it into a tablet to make an electrode.
[0191] 6.4. Recovery of Metals from Copper Anode Mud
[0192] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 120-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:6. In the H2SO4-MnO2 system, MnO2 accounts for 40% of the dry weight, and the H2SO4 concentration is 1.4 mol / L. During leaching, the leaching temperature is 75°C, the stirring speed is 600 r / min, and the leaching time is 8 h to obtain an anode mud leachate.
[0193] B2. Recover Au. Control the temperature of the anode mud leachate to 40°C and the pH to 3.0 (the pH can be adjusted by a low-concentration sodium hydroxide solution, such as a 5% by mass sodium hydroxide solution). Immerse the cathode in the anode mud leachate for 12 hours without an external power supply to enrich the Au in the anode mud leachate for the first time. Then, use the graphite electrode as the anode and apply a 1.6V power supply to continue enriching the Au in the anode mud leachate for 25 minutes, and then enrich the Au in the anode mud leachate for the second time.
[0194] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without power supply, and the anode mud leachate after enrichment with power supply were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 6 below. The test values in Table 6 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0195] Table 6 Example 6 process detection data table:
[0196] content Au Ag Se Te Bi Copper anode mud 2.4% wt 10.5% wt 9.2% wt 1.7% wt 1.3% wt Target powder 2.8% wt 13.8% wt 10.1% wt 1.9% wt 1.4% wt Anode mud leachate 2.6% wt 11.6% wt 10.2% wt 1.2% wt 1.6% wt Anode mud leachate after enrichment without power supply 2.1% wt 9.3% wt 8.2% wt 0.9% wt 1.2% wt Anode mud leachate after power supply enrichment 0.2% wt 6.5% wt 7.4% wt 0.6% wt 0.9% wt
[0197] It can be seen from Table 6 that without an external power supply, the Au enrichment effect reached 19%; then, with an external power supply for enrichment treatment, the Au enrichment effect reached 92%.
[0198] Example 7:
[0199] 7.1 Raw materials:
[0200] Hydrophobic ionic liquid: [C8Py][BETI] (cation: N-octylpyridinium anion: [BETI] - ); its weight percentage is 50%;
[0201] Porous conductive material: porous conductive ceramic; the weight percentage is 45%;
[0202] Packaging material: perfluorosulfonic acid polymer; the weight percentage is 5%;
[0203] 7.2 Preparation of cathode materials
[0204] A1, 0.03 g, and 23 μL of hydrophobic ionic liquid were placed in a glass bottle, and 0.027 g of porous conductive material was slowly added while stirring at a stirring rate of 4000 rpm. After the addition, the porous conductive material was stirred at room temperature for 0.5-1.5 hours. The temperature was then raised to 40°C, and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure environment of 0.8 MPa for 22 hours to allow the hydrophobic ionic liquid to fully penetrate the pores of the porous conductive material. The material was then filtered and dried in a vacuum environment at a temperature of 60°C for 1 hour to obtain the treated porous conductive material.
[0205] A2. Immerse the porous conductive material treated in step A1 in a packaging material solution for 60 minutes. The packaging material solution is a 2% by weight perfluorosulfonic acid polymer solution prepared by 0.003 g of perfluorosulfonic acid polymer and pure water. After the immersion is completed, take it out and then dry it in a vacuum environment at a temperature of 60°C for 1 hour to obtain a cathode material.
[0206] 7.3. Preparation of cathode
[0207] Take 100 mg of the cathode material prepared in 7.2 and press it into a tablet to make an electrode.
[0208] 7.4. Recovery of Metals from Copper Anode Mud
[0209] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 120-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:7.5. In the H2SO4-MnO2 system, MnO2 accounts for 45% of the dry weight, and the H2SO4 concentration is 1.0 mol / L. During leaching, the leaching temperature is 65°C, the stirring speed is 500 r / min, and the leaching time is 12 h to obtain an anode mud leachate.
[0210] B2. Recover Ag by controlling the temperature of the anode mud leachate to 30°C and the pH to 1.5 (the pH can be adjusted by a low-concentration sodium hydroxide solution, such as a sodium hydroxide solution with a mass percentage concentration of 5%). Without an external power supply, immerse the cathode in the anode mud leachate for 12 hours to enrich the Ag in the anode mud leachate for the first time. Then, use the Pt electrode as the anode and apply a 1.6V power supply to continue enriching the Ag in the anode mud leachate for 60 minutes, and then enrich the Ag in the anode mud leachate for the second time.
[0211] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without power supply, and the anode mud leachate after enrichment with power supply were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 7 below. The test values in Table 7 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0212] Table 7 Example 7 process detection data table:
[0213] content Ag Au Se Te Bi Copper anode mud 21.2% wt 1.1% wt 11.3% wt 1.3% wt 1.3% wt Target powder 31.4% wt 1.3% wt 11.2% wt 1.9% wt 1.7% wt Anode mud leachate 30.5% wt 1.2% wt 10.2% wt 1.7% wt 1.6% wt Anode mud leachate after enrichment without power supply 21.2% wt 1.1% wt 9.7% wt 1.4% wt 1.1% wt Anode mud leachate after power supply enrichment 0.7% wt 0.8% wt 6.2% wt 0.9% wt 0.8% wt
[0214] It can be seen from Table 7 that without an external power supply, the Ag enrichment effect reached 30%; then, with an external power supply for enrichment treatment, the Ag enrichment effect reached 98%.
[0215] Example 8:
[0216] 8.1 Raw materials:
[0217] Hydrophobic ionic liquids: [N 4441 ][BPh4] (cation: tetrabutylammonium anion: [BPh4] - ); its weight percentage is 55%;
[0218] Porous conductive material: porous conductive ceramic; its weight percentage is 42%;
[0219] Packaging material: perfluorosulfonic acid polymer; the weight percentage is 3%;
[0220] 8.2 Preparation of cathode materials
[0221] A1, 0.092 g, and 76.7 μL of hydrophobic ionic liquid were placed in a glass bottle, and 0.07 g of porous conductive material was slowly added while stirring at a stirring rate of 3000 rpm. After the addition, the porous conductive material was stirred at room temperature for 1 hour; then the temperature was raised to 60°C, and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure environment of 0.5 MPa for 24 hours to allow the hydrophobic ionic liquid to fully enter the pores of the porous conductive material; the mixture was filtered, and then dried in a vacuum environment at a temperature of 60°C for 1 hour to obtain the treated porous conductive material;
[0222] A2. Immerse the porous conductive material treated in step A1 in an encapsulation material solution for 60 minutes. The encapsulation material solution is a perfluorosulfonic acid polymer solution prepared by 0.005 g of perfluorosulfonic acid polymer and pure water with a weight percentage concentration of 1%-10%. After the immersion is completed, take it out and then dry it in a vacuum environment at a temperature of 60°C for 1 hour to obtain a cathode material.
[0223] 8.3. Preparation of cathode
[0224] Take 100 mg of the cathode material prepared in 8.2 and press it into a tablet to make an electrode.
[0225] 8.4. Recovery of Metals from Copper Anode Mud
[0226] B1. Dry and grind the copper anode mud. Sieve the ground powder with a 120-mesh sieve. The sieved material is the target powder. The target powder is acid-leached with a H2SO4-MnO2 system. The solid-liquid mass ratio of the target powder to the H2SO4-MnO2 system is 1:7.5. In the H2SO4-MnO2 system, MnO2 accounts for 40% of the dry weight, and the H2SO4 concentration is 1.4 mol / L. During leaching, the leaching temperature is 85°C, the stirring speed is 750 r / min, and the leaching time is 4 h. Then, obtain the anode mud leachate.
[0227] B2. Recover Ag and control the pH to 1.5 (the pH can be adjusted by a low-concentration sodium hydroxide solution, such as a 5% by mass sodium hydroxide solution). Without an external power supply, immerse the cathode in the anode mud leachate for 12 hours to enrich the Ag in the anode mud leachate for the first time. Then, use the lead dioxide electrode as the anode and apply a 1.6V power supply to continue enriching the Ag in the anode mud leachate for 20 minutes, and then enrich the Ag in the anode mud leachate for the second time.
[0228] In this embodiment, the copper anode mud, the target powder, the anode mud leachate, the anode mud leachate after enrichment without power supply, and the anode mud leachate after enrichment with power supply were respectively tested for element content (using atomic absorption spectrometry). The test results are shown in Table 8 below. The test values in Table 8 are all mass percentages of the elements. The remainder less than 100% is the content of Cu and HO.
[0229] Example 8 process detection data table:
[0230] content Ag Au Se Te Bi Copper anode mud 25.6% wt 1.7% wt 10.1% wt 1.1% wt 1.8% wt Target powder 23.1% wt 2.1% wt 10.6% wt 1.9% wt 2.1% wt Anode mud leachate 26.7% wt 1.8% wt 10.1% wt 1.7% wt 1.9% wt Anode mud leachate after enrichment without power supply 21.5% wt 1.1% wt 9.2% wt 1.4% wt 1.1% wt Anode mud leachate after power supply enrichment 0.7% wt 0.9% wt 8.5% wt 0.7% wt 0.8% wt
[0231] It can be seen from Table 8 that without an external power supply, the Ag enrichment effect reached 19%; then, with an external power supply for enrichment treatment, the Ag enrichment effect reached 97%.
[0232] 2. Experimental example:
[0233] The cathode prepared in Example 1 was used for application experiments. The cathode was electroplated in a simulated solution of copper anode mud leachate to extract Au. 3+ In the experiment, the simulated solution of copper anode mud leaching solution contained 0.1 M AuCl3 and 0.1 M CuSO4. 3+ The concentration of 50 mM was used for Au extraction experiments.
[0234] 1. Preparation of cathode materials
[0235] A1, 0.071 g, and 54.7 μL of a hydrophobic ionic liquid ([HMIm] Tf2N) were placed in a glass bottle. 0.067 g of a porous conductive material was slowly added while stirring at a stirring rate of 2000 rpm. The material was stirred at room temperature for 0.5 h. The temperature was then raised to 80°C, and the porous conductive material was immersed in the hydrophobic ionic liquid under a negative pressure of 0.3 MPa for 26 h to allow the hydrophobic ionic liquid to fully penetrate the pores of the porous conductive material. The material was then filtered and dried in a vacuum environment at 65°C for 0.5 h to obtain the treated porous conductive material.
[0236] A2. Immerse the porous conductive material treated in step A1 in a packaging material solution for 90 minutes. The packaging material solution is a 10% by weight fluorinated ethylene propylene copolymer solution prepared by 0.003 g of fluorinated ethylene propylene copolymer and pure water. After the immersion is completed, take it out and then dry it in a vacuum environment at a temperature of 65°C for 0.5 h to obtain a cathode material.
[0237] 2. Preparation of cathode
[0238] Take 100 mg of the cathode material prepared in 1 and press it into a tablet to form an electrode.
[0239] 3. Cathode cycle test
[0240] The temperature of the simulated solution is controlled to room temperature and the pH is 3.0 (the pH can be adjusted by a low concentration of sodium hydroxide solution, such as a sodium hydroxide solution with a mass percentage concentration of 5%). The lead dioxide electrode is used as the anode and an external voltage is applied to enrich the Au in the simulated solution.
[0241] The process of the cycle test is as follows: applying voltage to the cathode to enrich Au, and then regenerate; enriching Au again on the regenerated electrode, and then regenerating, and so on;
[0242] The enrichment method of Au is to apply a voltage of 1 V for 5 min each time and measure the Au content in the solution. 3+ The concentration is used to obtain the enrichment efficiency of the electrode;
[0243] The electrode regeneration method is to regenerate by applying a reverse current after enrichment, with an applied voltage of 1 V and a duration of 5 min.
[0244] like Figure 3As shown in the figure, the electrode can still maintain an enrichment efficiency of more than 70% after 10 cycles. The performance decline may be due to the loss of ionic liquid during the regeneration process by applying a reverse current or the incomplete regeneration process.
[0245] like Figure 4 As shown in the figure, it is the infrared structural information of the ionic liquid inside the cathode before and after the first voltage application. The comparison shows that the relevant stretching vibration peaks of the ionic liquid are basically unchanged, which proves the stability of the cathode. The stretching vibration peak of the ether oxygen bond in the system changes from 992 cm -1 Shift to 981 cm -1 This may be due to the complexation reaction between the oxygen atom on the ether oxygen bond and the metal ion, which also shows the chemical selectivity of our liquid cathode for metal ions. It also shows that the electrode regeneration process is not complete, and the regeneration time should be appropriately extended in subsequent use.
[0246] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with this technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be covered by the scope of protection of the present invention.
Claims
1. A cathode material, characterized in that Its preparation includes hydrophobic ionic liquid, porous conductive material and packaging material; Wherein, the hydrophobic ionic liquid is filled in the pores of the porous conductive material; The packaging material is coated on the outside of the porous conductive material to encapsulate the hydrophobic ionic liquid in the pores of the porous conductive material.
2. The cathode material according to claim 1, characterized in that The weight percentage of the hydrophobic ionic liquid is 45%-55%, The weight percentage of the porous conductive material is 35%-45%, The weight percentage of the packaging material is 1%-5%; The sum of the mass percentages of the hydrophobic ionic liquid, the porous conductive material and the packaging material is 100%.
3. The cathode material according to claim 1, characterized in that The hydrophobic ionic liquid comprises: a) The cationic portion is a derivative cation with an imidazolium cation as a skeleton, modified by any one or more of an amino group, a quaternary ammonium group, a quaternary phosphonium group, a thiourea substituent, a thioether substituent, a sulfhydryl group, a disulfide functional group, and a metal ion chelating group; b) The anion portion is at least one selected from bis(trifluorosulfonyl)imide, tetrafluoroborate, hexafluorophosphate, hypochlorite, trifluoroacetic acid, dicyandiamide, bromide, and chloride.
4. The cathode material according to claim 1, characterized in that The porous conductive material is selected from any one of metal-based porous materials, carbon-based porous materials, metal-organic framework derivatives and porous conductive ceramics; And / or, the packaging material includes a hydrophobic organic polymer material.
5. The cathode material according to claim 4, characterized in that The packaging material is selected from any one of polytetrafluoroethylene, fluorinated ethylene propylene copolymer, perfluoroalkoxy resin and perfluorosulfonic acid polymer.
6. The method for preparing a cathode material according to any one of claims 1 to 5, characterized in that: The steps include: A1. Immersing the porous conductive material in a hydrophobic ionic liquid so that the hydrophobic ionic liquid fully enters the pores of the porous conductive material; A2. Coating a packaging material layer on the outside of the porous conductive material treated in step A1, and drying the layer to obtain a cathode material.
7. The method for preparing a cathode material according to claim 6, wherein: In step A1, the immersion is carried out under a negative pressure of 0.3-0.8 MPa for 22-26 hours; And / or, in step A2, coating the encapsulation material layer is performed by immersing the porous conductive material treated in step A1 in an encapsulation material solution, wherein the weight percentage concentration of the encapsulation material solution is 1%-10%; And / or, in step A2, the drying is carried out in a vacuum environment at a temperature of 55-65° C. for 0.5-1.5 hours.
8. A cathode, characterized in that The cathode material is prepared by the preparation method according to any one of claims 6 to 7.
9. A method for recovering metals from copper anode mud, characterized in that: The steps include: B1. Grind, sieve and acid-leach the copper anode mud to obtain anode mud leachate; B2. Controlling the temperature of the anode mud leachate obtained in step B1 to be 15-60° C. and the pH to be 0-7, then placing the cathode described in claim 8 in the anode mud leachate and soaking it for 0.5-36 hours to perform a first enrichment of rare and precious metals in the anode mud leachate; then, connecting an external power supply in the presence of the anode and applying a voltage of 1-30 V to perform a second enrichment of rare and precious metals in the anode mud leachate.
10. The method for recovering metals from copper anode mud according to claim 9, characterized in that: In the step B1, during acid leaching, the solid-liquid mass ratio of the sieved copper anode mud powder to the H2SO4-MnO2 system is 1:5-1:10; And / or, in step B1, the acid leaching adopts a H2SO4-MnO2 system, in which MnO2 accounts for 40-70% of the dry basis weight and the H2SO4 concentration is 0.7-1.4 mol / L; And / or, in step B1, during acid leaching: the leaching temperature is 65-85° C., the stirring speed is 500-750 r / min, and the leaching time is 4-12 h; And / or, in step B2, the anode is selected from any one of a graphite electrode, a Pt electrode and a lead dioxide electrode; And / or, in step B2, the rare metals enriched for the first time and the rare metals enriched for the second time are the same.